The long-term impact of postoperative pulmonary complications after video-assisted thoracic surgery lobectomy for lung cancer - Wang, Shaodong; Li, Xiao; Li, Yun; Li, Jianfeng; Jiang, Guanchao; Liu, Jun; Wang, Jun (Journal of Thoracic Disease; Vol 9, No 12 (December 29, 2017): Journal of Thoracic Disease, 2017)
Background: Pulmonary complications (PCs) may influence long-term survivor. We sought to determine the long-term impacts of major pulmonary complications (MPCs) and identify the independent risk factors in non-small cell lung cancer (NSCLC) patients. Methods: A retrospective study was conducted to analyze the PCs of 828 NSCLC patients who underwent video-assisted thoracic surgery (VATS) lobectomy in Peking University Hospital, the complications were graded according to TMM classification. The effects of PCs on the long-term prognosis were analyzed by using the Kaplan-Meier method. Multivariate logistic regression analysis was used to determine the risk factors of MPCs. Results: Of 828 patients, 139 had PCs, including 66 (8%) MPCs, those patients who developed a PC had longer drainage time, hospital stay and higher perioperative mortality rate. Excluding perioperative deaths, those who develop a MPC had a reduced 3-year disease-free survival (DFS) and 5-year DFS (68.2% vs. 78.7%, 44.7% vs. 70.3%; P=0.001), as well as the reduced 3-year overall survival (OS) and 5-year OS (81.8% vs. 88.6%, 66.6% vs. 80.9%; P=0.023). MPCs were independent prognostic factors of patients with lung cancer. Multivariate logistic regression analysis showed that the independent risk factors for MPCs were age [P=0.007; hazard ratio (HR): 1.05, 95% confidence interval (CI): 1.01–1.08], male (P=0.001; HR: 3.33, 95% CI: 1.87–5.94) and American Society of Anesthesiologist (ASA) grade. Conclusions: MPC after VATS lobectomy is associated with a poorer long-time outcome. The independent risk factors for MPCs were age, male and ASA grade.